Bacterial Proliferation in Municipal Water Supplied in Mirpur Locality of Dhaka City, Bangladesh. Issue 4 (30th August 2013) - Acharjee, Mrityunjoy; Rahman, Farjana; Jahan, Fahmida; Noor, Rashed
<x xml:space="preserve">Abstract</x> Water related environmental pollution has long been a major concern not only in Bangladesh but also in other developing countries. Present study assessed the pathogenic prevalence in municipal water supplied across Mirpur zone, Dhaka, and its subsequent health impact on the local community. Elevated numbers of pathogenic bacteria including Aeromonas spp., Shigella spp., Staphylococcus spp., and Salmonella spp. were found in the consumer points (n = 30) compared to that of the supply points (n = 10). Additionally, proliferation of fecal coliforms, Escherichia coli and Klebsiella spp. was monitored among the consumer points and not in the supply points. Drug resistance was scored against ampicillin (10 µg), ciprofloxacin (5 µg), ceftriazone (30 µg), penicillin (10 µg), nalidixic acid (30 µg), and vancomycin (30 µg). Hence, the municipal water of the study area was microbiologically unsafe, and the propagation of drug resistant strains was assumed to escalate the public health threat. A survey on public opinions was also conducted to evidently chalk out the impact of municipal water on the specific community studied.